Union Strategy and Optimal Income Taxation - Sebastian G. Kessing; Kai A. Konrad (Institute for the Study of Labor (IZA), 2005)
Restrictions on work hours are more important in countries with a large welfare state. We show that this empirical observation is consistent with the strategic effects of such restrictions in a welfare state in the context of optimal direct taxation in the tradition of Mirrlees (1971). Our results also apply to non-welfarist states which have income redistribution, but not in purely extortionary states.
Keywords: H23; H21; 330; optimal income taxation; labor unions; work hours; Einkommensteuer; Optimale Besteuerung; Arbeitszeitflexibilisierung; Gewerkschaftspolitik; Soziale Wohlfahrtsfunktion; Einkommensumverteilung; Wohlfahrtseffekt; Theorie